Member-International Civil Aviation Organization Training Packages Development: Population Analysis - Oka, I Gusti Agung Ayu Mas; Leonaldy, Sugeng (Langit Biru: Jurnal Ilmiah Aviasi, 2024)
The aim of this study was to conduct a population analysis as part of the Member-International Civil Aviation Organization Training Packages (M-ITP) development, which involved collecting information about the target population (prospective trainees) to identify their existing competencies, preferred learning styles, and social and cultural backgrounds. This study was conducted using a qualitative approach with a survey method as the data collection technique. The results of this study concluded that: 1) respondents were of productive age and had a sufficient educational background, 2) most respondents had not attended Training and Procedure Manual (TPM) development training and struggled to find information on how to develop TPM, indicating a strong demand for such training, 3) the majority of respondents believed that training was necessary to enhance their job performance, with an ideal training duration of 4 to 10 days, 4) while respondents occasionally engaged in self-study through reading technical literature, they faced significant challenges, suggesting that self-study was not well-suited for them, and 5) the preferred learning methods were instructor-led, competency-based scenario training, lectures, or demonstrations and practical exercises.